Crystal growth of La2/3-xLi3xTiO3 by the TSFZ method. Issue 12 (5th December 2018) - Maruyama, Yuki; Minamimure, Shiho; Kobayashi, Chinatsu; Nagao, Masanori; Watauchi, Satoshi; Tanaka, Isao
Abstract : Double-perovskite-type La2/3- x Li3 x TiO3 (LLT) crystals were grown by the travelling solvent floating zone (TSFZ) method. When the floating zone (FZ) crystal growth method was applied, the La2 Ti2 O7 phase was deposited as an inclusion in the initial growth region. Using the TSFZ crystal growth method, however, inclusion-free LLT crystals were obtained for a 10 mol% La2 Ti2 O7 -poor composition solvent relative to the stoichiometric LLT crystals. The molten zone was initially unstable as a result of habit plane formation during the crystal growth; however, the molten zone was stably maintained for a long period of time by decreasing the feed rate compared with the growth rate. Hence, LLT crystals of approximately 5 mm φ and 37 mm in length were obtained. The anisotropic ionic conductivity of the crystals annealed in air was σ [110]/ σ [001] ≈ 3, with σ [110] = 1.64 × 10 −3 S cm −1 and σ [001] = 5.26 × 10 −4 S cm −1 . LLT single crystals are candidates for high-performance solid-state electrolytes in all-solid-state Li ion batteries.